Cross-border healthcare for all EU residents? Linguistic access in the European Union. Issue 2 (2nd October 2017) - Angelelli, Claudia
Abstract : In 2011, the European Union introduced a Directive to facilitate cross-border healthcare, thus enhancing options for EU citizens and residents who are able to travel. However, if healthcare services are provided in a language patients cannot fully understand, equal access to safe and high-quality healthcare cannot be guaranteed. This exploratory study examines provisions for linguistically diverse patients seeking cross-border healthcare in areas of Germany, Greece, Italy, Spain and the UK. To address the language needs of these patients, healthcare organisations resort to a number of strategies, ranging from monolingual communication matching the language of the patient, to professional translation, interpreting and cultural mediation, or to informal and non-professional ad hoc solutions. In the absence of formal language guidance in EU legislation, in most observed cases appropriate language services are not provided for patients who are not proficient in the language of the Member State in which they seek healthcare. This study raises ethical questions regarding access and communication and has implications for policy makers, healthcare providers, educators, translators, interpreters and cultural mediators serving the needs of linguistically and culturally diverse patients.